Estresse oxidativo e efeitos comportamentais resultantes da inibição crônica do complexo i mitocondrial por rotenona - FERREIRA, Daniel Arnaud Pereira (2023)
Rotenone, an active ingredient extracted from tropical plants such as timbo, is a substance widely used in the Amazon region as a pesticide in the regional fishing. This neurotoxic reproduces many aspects of Parkinson's Disease (PD) in animal models in vivo and in vitro, including nigrostriatal dopaminergic degeneration and formation of cytoplasmic inclusions similar to Lewy bodies. One hypothesis is that exposure to environmental factors, along with aging and genetic factors increase the risk of disease development. By causing changes in oxidative metabolism, since it is an inhibitor of mitochondrial complex I, rotenone increases the production of reactive oxygen species (ROS). The excess of ROS has detrimental effects such as peroxidation of membrane lipids and aggression to tissue proteins and membranes. The consequences of oxidative stress in neurons of the nigrostriatal pathway lead to changes of motion, balance and changes in fine motor control. In this study, male Wistar rats, divided into control groups (n = 12) and treated (n = 13) underwent intraperitoneal administration of rotenone for 30 days. We evaluated the occurrence of lipid peroxidation in brain regions directly involved in PD as the substantia nigra and the striatum as well as other regions such as cerebral cortex, cerebellum, hippocampus and hypothalamus. Cortex, cerebellum, striatum and substantia nigra were the areas where there was statistical difference in outcomes between treated and control groups. Behavioral tests performed in the first, fifteenth and thirtieth days, showed motor abnormalities including decreased locomotor activity and decreased ability to adopt a standing position with and without support. So it is not possible to rule out the possibility that such changes are a result of dysfunction in multiple functions in various areas of the nervous system, including or not the nigrostriatal pathway. As the mechanisms of toxicity induced by rotenone are still not fully understood, this study aimed to further investigate the induction of oxidative stress in peripheral tissues. Tissues analyzed included the proximal duodenum, liver and kidney. The results showed some degree of peroxidation mainly in liver and kidney.